On the Stock Market-Electricity Sector Nexus in Latin America: A Dynamic Panel Data Model - Aali-Bujari, AlÃ; Venegas-MartÃnez, Francisco; Santillán-Salgado, Roberto J. (International Journal of Energy Economics and Policy, 2018)
The aim of this paper is to assess the impact of the stock market on the consumption of electric power in the major economies of Latin America during the period 1995-2014. To do this, a dynamic panel data model is estimated through the generalized method of moments. The main empirical finding is that electric power consumption is positively affected by the stock market indices of Argentina, Brazil, Chile, Colombia, Ecuador, Mexico, Peru, and Costa Rica. Keywords: Electricity consumption, stock markets, dynamic panel data. JEL Classifications: G10, G15, C33, Q40. DOI: https://doi.org/10.32479/ijeep.7120